1975
DOI: 10.1021/jm00245a002
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic binding site in acetylcholinesterase

Abstract: The dissociation constants have been determined and compared for a series of reversible, noncovalent inhibitors of eel acetylcholinesterase that are structurally related to the very potent inhibitor, 1,2,3,4-tetrahydro-9-aminoacridine (THA). It is concluded that there exists on the enzyme protein, closely adjacent to the anionic subsite, a conformationally flexible, hydrophobic area which tends readily to assume a near planar form. The dimensions of this area are unknown, but it is adequate in size to fully ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(31 citation statements)
references
References 2 publications
5
25
1
Order By: Relevance
“…It is clear that THA is not an irreversible inhibitor of acetylcholinesterase, as the inhibition was not timedependent and was rapidly reversible by dilution. The results indicate that THA does not bind to the catalytic ('esteratic') site and it has been suggested by others (Steinberg et al, 1975) Freedman et al, 1988).…”
Section: Discussionsupporting
confidence: 76%
“…It is clear that THA is not an irreversible inhibitor of acetylcholinesterase, as the inhibition was not timedependent and was rapidly reversible by dilution. The results indicate that THA does not bind to the catalytic ('esteratic') site and it has been suggested by others (Steinberg et al, 1975) Freedman et al, 1988).…”
Section: Discussionsupporting
confidence: 76%
“…This mechanism of action does not appear in Iine with reports indicating that THA interacts with AChE in a noncompetitive way (Hunter et al 1989;Wu and Yang 1989). However, this point is still controversial since according to Steinberg et al (1975), Nielsen et al (1989) and to our own experiments (unpublished observation), there is a substantial component of competitive action on THA's inhibitory effect. Finally, also the possibility that mechanism(s) other than AChE protection may be involved in THA antidotal action, deserves attention.…”
Section: Discussionmentioning
confidence: 87%
“…THA is a polycyclic primary amine endowed with potent inhibitory activity towards both AChE and butyrylcholinesterase (BuChE; EC 3.1.1.8) (Kaul 1962;Steinberg et al 1975;Hunter et al 1989). Interest in this drug arises mainly from reports indicating that is effective in improving the clinical condition of certain patients with Alzheimer's disease (Summers et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that nicotine will stimulate striatal 5-HT release (Westfall et al, 1983). In addition to its inhibitory activity against AChE (Shaw & Bentley, 1953;Steinberg et al, 1975) THA is centrally active at both muscarinic and, more weakly, at nicotinic receptors (Nilsson et al, 1987;Hunter et al, 1989;Perry et al, 1988;Pearce & Potter, 1988). It was feasible therefore that THA might modulate monoamine release via ACh receptors, either through a direct action or by increasing the concentration of ACh.…”
Section: Effect Of Tha On S-ht Reuptakementioning
confidence: 99%